SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMAAN RASKIN DI MENGGUNAKAN METODE TOPSIS - Masitah Handayani (Universitas Asahan, 2017)
Abstract - During this time in the village of Mekar Sari in making decisions for Raskin revenue still using manual methods. The problem is the difficulty in storing or searching the archives that have been stored, as well as the problem of making late reports that also hamper the delivery of information. Many families should not get Raskin but receive raskin too, on the contrary for poor families who should get Raskin but not get it. this research was conducted with the aim of developing a decision support system application that facilitates the parties to make decisions in the selection of poor families who are entitled to receive Raskin in Mekar Sari Dusun Village. The method used in system development is the TOPSIS method, where the topsis method is is one of the decision making methods where the chosen alternative is the best alternative that has the closest distance from the positive ideal solution and the farthest from the negative ideal solution. Keywords - Raskin, decision support system, TOPSIS.